Fundamental neuroscience for basic and clinical applications - Haines, Duane E (Elsevier Saunders, 2013)
Includes coverage of neuroanatomy, physiology, and pharmacology, with a particular emphasis on systems neurobiology, effectively prepares you for your courses, exams, and beyond.